Violation of the Principle of Cooperation and Implicature in the Drama One Liter of Tears - Eko Kurniawan; Ita Fitriana; Chendy Arieshanty Paramytha Sulistyo; Anggita Stovia (Universitas Muhammadiyah Yogyakarta, 2024)
The objective of this study is to provide a description of the various instances where the cooperation principle is violated and implicatures are present in the drama One Litre of Tears. The data on violation of the cooperation principle and implicatures are analyzed using Grice's theory of cooperation principle (1975) and Yule's theory of implicatures (2006). This research is a descriptive study conducted using a qualitative approach. The primary data source utilized in this study is the television drama series titled